The Association of Nil Per Os (NPO) Days with Necrotizing Enterocolitis - Wang, Yongming (Gastroenterol Res Pract, 2018)
BACKGROUND: Enteral feeds are an essential part of care for infants and may be a potential risk factor in NEC development. The present study objective was to evaluate the relationship between nil per os (NPO) and clinical outcomes in infants with NEC. METHODS: This was a retrospective review of 196 premature, low-birth-weight infants with NEC from January 1, 2011, to October 31, 2016, at four academic tertiary care hospitals. The patients were evaluated based on the median nil per os (NPO) days (5.6 days) in longer NPO (6.3 ± 1.1 days) versus shorter NPO groups (4.2 ± 0.9 days). RESULTS: Patients who experienced longer than 5.6 NPO days were more likely associated with perforated NEC (odds ratio (OR), 2.01; 95% confidence interval (CI), 1.07–3.76; p = 0.021), stage III NEC (OR, 1.81; 95% CI, 0.97–3.38; p = 0.042), and longer duration of mechanical ventilation (OR, 0.17; 95% CI, 0.08–0.98; p = 0.005) than the shorter duration group of 5.6 NPO days. For the secondary outcomes, there was a trend towards earlier birth (p = 0.083), longer NICU length of stay (p = 0.093), and higher mortality (p = 0.10) in the longer NPO cohort (p = 0.057). The incidence of bacterial sepsis and short bowel syndrome also increased as the length of NPO increased. There was no statistically significant difference in nutritional variables between the two groups within the in-hospital period. CONCLUSION: Longer NPO time was associated with the severity of NEC and more injurious clinical outcomes, as demonstrated by rates of surgical intervention and duration of mechanical ventilation.